Aplikasi Taqdim Wa Takhir Fii Juz Amma (Kajian Uslubiyah) - Hamidi, Saddam Reza; Mubarok, Muhammad Husnil; Muassomah, Muassomah (Universitas Muhammadiyah Gorontalo, 2023)
Priority And Delay is an Arabic style that prioritizes or ends lafadz with certain causes and purposes. The aims of this study are (1) to determine the form of taqdim wa takhir fii Juz Amma; (2) to find out the cause of Priority And Delay In Juz Amma. This study used qualitative research methods. The object of this research study is juz 30 in the Qur'an or known as Juz 'Amma. Data analysis by collecting data followed by classifying and identifying data, presenting data, and drawing conclusions. The result of this research is the discovery of 3 forms of Priority And Delay In Juz Amma and 5 causes of Priority And Delay In Juzz Amma.